Evolution and Facies Architecture of A Himalayan Cretaceous Forearc Basin - G. Einsele et al. (Ikatan Ahli Geologi Indonesia, 1998)
The mid-Cretaceous to Eocene flysch deposits of the Xigaze forearc basin in southern Tibet were investigated in a 120 km segment along the Indus Yarlung suture zone. The basin evolved south of the magnetic arc (Gangdise belt) of the Lhasa block on top of trapped oceanic or transitional crust.